Behavior of Laterally top-Loaded Drilled Piles in Collapsible Tropical Soil (London Journal of Engineering Research, 2023)
Among the various types of loading to which foundations are subject, one can single out transversal (horizontal) forces. In general terms, we notice a lack of knowledge on the parameters used to design pile foundations with this type of load which will stress surface soil, considering that tropical soils are very often collapsible. Aiming to furnish input for future geotechnical projects, transversal loading tests were performed on a bored pile and a continuous flight auger (CFA) pile, both 12.0 m in length, and 0.40 m in diameter. The loading tests were performed with the soil in its natural condition and by pre-flooding the area, at the UNICAMP Experimental Soil Mechanics and Foundations Field I in Campinas/SP, Brazil, where the unsaturated soil is porous and classified as silty-sandy clay. The edometric tests indicated that is a collapsible soil in the surface bed up to 6.5m, and that the reduction in pre-collapse stress in the flooded condition is of the order of three times that of the natural condition. The load tests indicated that the maximum load in the natural condition is five times higher than in the flooded condition and that the value of n h (horizontal reaction coefficient) reduces substantially with the effect of increasing soil moisture content.